Rancang Bangun Pompa Hidram Untuk Eduwisata Pemandian Sumberingin Desa Wringinsongo Tumpang Kabupaten Malang - Andi Ardiansyah; Bagus Wahyudi (Jurnal Kendali Teknik dan Sains, 2025)
This study discusses the effect of valve weight and clearance on the efficiency of a hydraulic ram pump, with a focus on optimizing water discharge efficiency in the Sumberingin Tourism Area, Wringinsongo Village, Tumpang, Malang Regency. The method used in this study is an experiment with variations in valve weight consisting of 10 kg, 11 kg, and 12 kg, as well as valve clearances varying between 16.5 mm, 24.5 mm, and 32.5 mm. The results showed that the combination of a valve weight of 10 kg and a clearance of 16.5 mm produced the highest water discharge efficiency, namely 69.7 liters per minute, with an optimal efficiency of around 33%. In the optimization process, the application of Design of Experiment (DOE) revealed that a valve weight of 11 kg and a clearance of 16.5 mm can produce a maximum discharge efficiency of 63.155 with a desirability value reaching 0.7671. These findings indicate that proper settings on valve weight and clearance can contribute significantly to increasing the efficiency of a hydraulic ram pump. This research provides valuable insights into improving the performance and reliability of hydraulic ram pumps in rural water distribution systems. Understanding the influence of these variables is expected to yield more effective solutions for water resource management, particularly in areas requiring efficient irrigation systems. Furthermore, this research also opens up opportunities for further research on hydraulic ram pump optimization by considering other factors that can influence the efficiency and performance of the overall water distribution system. It is hoped that the results of this research can serve as a reference for the development of more efficient and environmentally friendly hydraulic ram pump technology, as well as supporting the sustainability of water resource management in rural areas.